Manajemen Pemulihan Ekosistem Cagar Alam Gua Nglirip - Tyas, Tria Agustining; Rahmawati, Laily Agustina (Universitas Bengkulu, 2024)
Gua Nglirip Nature Reserve was initially a conservation area rich in native flora, such as Weeping fig (Ficus benjamina) and Walen (Ficus ribes Reinw.). However, habitat destruction has led to the loss of native flora in the area. This study aimed to analyze ecosystem recovery management in the Gua Nglirip Nature Reserve, specifically emphasizing native flora rehabilitation. This research was conducted using a descriptive qualitative method, data was collected through interviews and document studies from key informants and official reports. The ecosystem recovery process was carried out in two rehabilitation blocks with a total area of 20,504 m², involving the replanting of lost native flora species, such as Weeping tree and Walen, with 836 seedlings planted across both blocks. However, challenges such as fires, prolonged drought, wildlife habitat disturbances, and insufficient monitoring and evaluation, particularly in documenting plant growth data, have caused delays in the ecosystem recovery process. The study results indicate that although progress has been made, improvements in management and better implementation are needed for long-term success.